Method for producing omniphobic cosmetic pigments.

By adsorbing partially or completely deacetylated poly(β-(1→4)-D-glucosamine chains on the surface of metal oxide particles, forming cosmetic particles with core-shell structures, the problem of cosmetics maintaining waterproof and oil-resistant properties on the skin for a long time is solved, and the use of harmful fluoride is avoided.

JP7628391B2Active Publication Date: 2025-02-10COMMISSARIAT A LENERGIE ATOMIQUE ET AUX ENERGIES ALTERNATIVES +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2019206295
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-11-15
Filing Date
2019-11-14
Publication Date
2025-02-10
Estimated Expiration
2039-11-14

AI Technical Summary

Technical Problem

The prior art is difficult to provide waterproof and oil-resistant cosmetic particles that can be maintained on human skin for a long time without avoiding the use of harmful fluorides.

Method used

By preparing a particle with a core of metal oxide, partially adsorbed or completely deacetylated poly(β-(1→4)-D-glucosamine chain with a core and a sudden change in pH value, a fully waterproof and oil-resistant cosmetic particles with a core-shell structure are formed.

Benefits of technology

It achieves the waterproof and oil-resistant properties on the skin for a long time, avoids the use of harmful fluorides, and maintains the excellent performance of cosmetics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628391000003
    Figure 0007628391000003
  • Figure 0007628391000004
    Figure 0007628391000004
  • Figure 0007628391000005
    Figure 0007628391000005
Patent Text Reader

Abstract

To provide a method for producing omniphobic pigment that can tolerate both sebum and sweat.SOLUTION: A method for producing pigment for omniphobic cosmetic includes: (i) a step of fabricating acid aqueous solution including metal oxide particles and poly(β-(1→4)-D-glucosamine) in which the poly(β-(1→4)-D-glucosamine) is acetylated or partially or completely deacetylated; and (ii) a step of increasing pH of solution obtained in step (i) to approximately 12 in order to make the poly(β-(1→4)-D-glucosamine) adsorbed onto metal oxide particles and sediment metal oxide particles coated with the obtained poly(β-(1→4)-D-glucosamine). It is preferable that poly(β-(1→4)-D-glucosamine) be chitosan.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THEINVENTION The present invention relates to the field of cosmetics. In particular, the present invention relates to omniphobic cosmetic pigments in the form of a core-shell structure, the core of which comprises or consists of metal oxides to which poly(β-(1→4)-D-glucosamine) chains are adsorbed, said chains being acetylated or partially or completely deacetylated. The present invention also relates to a method for the preparation of said omniphobic cosmetic pigments, and to their use. [Background technology]

[0002] Inorganic pigments are widely used in cosmetics because they impart various properties to the products.

[0003] Inorganic cosmetic pigments are primarily oxides such as titanium dioxide (TiO2), iron oxides (eg Fe3O4) or hydroxylated magnesium silicates.

[0004] Whatever the pigment, consumers want optimal retention of the pigment on their skin, but the skin is a complex organ, secreting both sebum (equivalent of a lipid medium) and sweat (equivalent of an aqueous medium).

[0005] Thus, there remains a need to provide cosmetic pigments that are optimized for long-lasting pigment retention on the consumer's skin, in particular to provide omniphobic cosmetic pigments, i.e. pigments that are suitable for human skin and can withstand both sebum and sweat, in the sense that these liquids do not spread on the pigment.

[0006] Some attempts have been made to modify the surface of metal oxide particles with fluorinated compounds such as perfluorooctanoic acid (PFOA), but recent studies have clearly demonstrated the increased risk of cancer caused by fluorinated compounds, as well as their adverse environmental effects.

[0007] Thus, there is a pressing need to provide omniphobic cosmetic pigments while avoiding fluorinated molecules such as those mentioned above.

[0008] Surprisingly, the applicant has demonstrated that cosmetic pigments comprising a metal oxide core to which are adsorbed partially or fully N-acetylated poly(β-(1→4)-D-glucosamine) chains have omniphobic properties. The cosmetic pigments of the present invention are prepared by a special method involving a precipitation step by abrupt change in the pH of the reaction medium. Summary of the Invention

[0009] The present invention relates to a method for producing an omniphobic cosmetic pigment, said method comprising the steps of: (i) preparing an acidic aqueous solution containing metal oxide particles and poly(β-(1→4)-D-glucosamine), wherein the poly(β-(1→4)-D-glucosamine) is acetylated or partially or completely deacetylated; and (ii) increasing the pH of the solution obtained in step (i) to about 12 in order to adsorb the poly(β-(1→4)-D-glucosamine) onto the metal oxide particles and to precipitate the resulting poly(β-(1→4)-D-glucosamine)-coated metal oxide particles.

[0010] In one embodiment, the metal oxide particles are selected from titanium oxide, iron oxide, zinc oxide, zirconium oxide, yellow iron oxide, black iron oxide, red iron oxide, chromium oxide, chromium hydroxide, ultramarine; silicates such as mica, sericite, kaolin, talc, aluminum silicate, magnesium silicate, calcium silicate or clay; preferably titanium oxide particles.

[0011] In one embodiment, the metal oxide particles have a size in the range of 100 nm to 100 μm, preferably 500 nm to 60 μm.

[0012] In one embodiment, the poly(β-(1→4)-D-glucosamine) is partially N-deacetylated, preferably chitosan. In one embodiment, the poly(β-(1→4)-D-glucosamine) is fully deacetylated or both deacetylated and acetylated; preferably chitosan.

[0013] In one embodiment, the poly(β-(1→4)-D-glucosamine) has a viscosity, measured at about 25° C., in the range of 10 cP to 2000 cP; preferably, 40 cP to 800 cP; more preferably, 50 cP to 350 cP.

[0014] In one embodiment, the poly(β-(1→4)-D-glucosamine) is partially deacetylated, having a degree of deacetylation in the range of 70% to 99%; preferably 75% to 95%; more preferably 75% to 85%.

[0015] In one embodiment, the poly(β-(1→4)-D-glucosamine) has a weight average molar mass (Mw) in the range of 40,000 Da to 500,000 Da; preferably 100,000 Da to 300,000 Da.

[0016] In one embodiment, the amount of poly(β-(1→4)-D-glucosamine) is in the range of from greater than 0% to 20% by weight, preferably in the range of from 1% to 15% by weight, and more preferably about 3% or 10% by weight, based on the total weight of the poly(β-(1→4)-D-glucosamine) and metal oxide particles.

[0017] In one embodiment, the acidic aqueous solution comprises an acid; preferably an organic acid; more preferably acetic acid.

[0018] The present invention relates to omniphobic cosmetic pigments obtained by the process according to the invention.

[0019] In one embodiment, the omniphobic cosmetic pigment comprises or consists of titanium oxide particles having chitosan chains adsorbed thereon.

[0020] The present invention relates to a cosmetic composition comprising the omniphobic cosmetic pigment of the present invention and a cosmetically acceptable base.

[0021] In one embodiment, the cosmetically acceptable base is anhydrous.

[0022] In one embodiment, the composition is in the form of an aqueous gel, an oily gel, a paste, a cream, a lotion, an emulsion, a stick, a soap, a foam, a shampoo, a compact powder, a loose powder, a nail polish, a cosmetic mask, an aerosol, a film, a serum, an emulsion, or a patch.

[0023] The present invention relates to a method for cosmetically improving the skin of a subject in need thereof, comprising the use of the omniphobic cosmetic pigment of the present invention or the cosmetic composition of the present invention.

[0024] In one embodiment, the composition is administered once daily to the skin of a subject in need thereof.

[0025] The present invention relates to the use of the cosmetic composition of the present invention in make-up, skin care, sun care, hair care, manicure, toiletries, baby care or pet care. [Brief description of the drawings]

[0026] [Figure 1] Photographs showing, from left to right, vials containing pure water and: uncoated TiO2 particles [TiO2]; TiO2 particles coated with chitosan A and washed once [TiO2+LV]; TiO2 particles coated with chitosan A and washed four times [TiO2+LV x4]; TiO2 particles coated with chitosan B and washed once [TiO2+MV] and TiO2 particles coated with chitosan B and washed four times [TiO2+MV x4]. [Diagram 2] Photographs showing vials containing pure water and chitosan-coated TiO2 particles obtained from a method (method of the present invention) with alkalinization at a pH of (from left to right): 6, 7 or 12. [Diagram 3] Photographs showing, from left to right, a mixture of pure water and isononyl isononanoate, and vials containing: uncoated TiO2 particles [TiO2]; TiO2 particles coated with chitosan A and washed once [TiO2+LV]; TiO2 particles coated with chitosan A and washed four times [TiO2+LV x4]; TiO2 particles coated with chitosan B and washed once [TiO2+MV] and TiO2 particles coated with chitosan B and washed four times [TiO2+MV x4]. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] definition In the present invention, the following terms have the meanings indicated therein. - The word "about" before a numerical value means ±10% of the value of said numerical value. "Acetic acid" or "ethanoic acid" means the organic compound having the formula CH3COOH. - "Acid" is a hydrogen ion (H + The term "anhydrous fluoride" refers to any compound that is capable of releasing an electron (Brønsted acid) or forming a covalent bond with an electron pair (Lewis acid). - "Adsorption" means the surface phenomenon in which atoms, ions or molecules (the adsorbate) bind to a solid surface (the adsorbent) from the gas phase, liquid solution or solid solution. "Anhydrous composition" means a composition which comprises less than 5% by weight of water, preferably less than 2% by weight of water, or even less than 0.5% by weight of water, based on the total weight of the composition, and in particular a composition which is free of water. "Chitin" means a naturally occurring polysaccharide that is poly(β-(1→4)-N-acetyl-D-glucosamine). In particular, "chitin" has the formula: [ka] In the formula, n is a positive integer, preferably in the range of 10 to 2,000. - "Chitosan" refers to a polysaccharide that is a random copolymer of β-(1→4)-N-acetyl-D-glucosamine and β-(1→4)-D-glucosamine (i.e., poly[(β-(1→4)-N-acetyl-D-glucosamine)-co-(β-(1→4)-D-glucosamine)]). The term "chitosan" also refers to deacetylated poly(β-(1→4)-D-glucosamine). "Cosmetic" refers to use to improve the aesthetic appearance or physical comfort of a subject. In one embodiment, the term "cosmetic" includes solar care, such as the use of solar creams. - "Cosmetically acceptable base" means any compound that does not induce any side effects, such as toxicity, irritation, inflammation or allergic reactions, for use in contact with the epidermis and / or dermis. In the present invention, cosmetically acceptable bases include bases for topical administration. In one embodiment, the expression "cosmetically acceptable base" means a carrier in which the pigment is dispersed, which does not induce any side effects, such as toxicity, irritation, inflammation or allergic reactions, for use in contact with the epidermis and / or dermis. "Degree of chitosan acetylation (DA)" means the percentage of N-acetylated units compared to the total number of units in the main chain of chitosan. "Degree of chitosan deacetylation (DD)" means the percentage of N-deacetylated units compared to the total number of units in the main chain of chitosan. "Cosmetic skin improvement method" means any cosmetic method that makes it possible to improve the aesthetic appearance of the skin of a subject. "Iron oxide" refers to a chemical compound made from oxygen and iron atoms. In one embodiment, "iron oxide" refers to a compound of the formula: FeO, Fe3O4, or Fe2O3. - "metal oxide" refers to a chemical compound made from a metal and oxygen. In one embodiment, the phrase "metal oxide" refers to any compound having an anionic portion that is an oxide and a cationic portion that is a metal. "Omniphobic" refers to a chemical compound or substance that has both hydrophobic and oleophobic properties. In one embodiment, the term "omniphobic" refers to a compound or substance that is only slightly wettable by sebum and sweat secreted by the skin of a subject. "Particle" means a compound that is spherical or of spherical or spheroidal morphology. In one embodiment, the term "particle" in the present invention means a spherical or spheroidal pigment. "pH" refers in chemistry to a scale measuring the acidity of a solution. In one embodiment, pH refers to a scale measuring the acidity of an aqueous solution, preferably ranging from 0 to 14. "Pigment" means a chemical coloring substance in the form of finely dispersed, non-agglomerated particles that are insoluble in the medium in which they appear. - "Poly(β-(1-4)-D-glucosamine)" means a polysaccharide obtained by polymerization of D-glucosamine units, in which two consecutive units are covalently linked to each other by a β,1-4 glycosidic bond. In one embodiment, the term "poly(β-(1-4)-D-glucosamine)" includes poly(β-(1-4)-N-acetyl-D-glucosamine) (also called "chitin") and partially or fully deacetylated poly(β-(1-4)-N-acetyl-D-glucosamine) (also called "chitosan"). "Precipitation" means the appearance of an insoluble solid from a liquid solution. "Particle size" means the average diameter of the particles. In the present invention, the particle size (or the average diameter of the particles) is preferably measured by dynamic light scattering (DLS) using a Malvern Zetasizer®. - "Subject" means a mammal, preferably a human, to whom the particles of the invention are administered. - "Titanium oxide" refers to a chemical compound made up of oxygen (O) and titanium (Ti) atoms. In one embodiment, the term "titanium oxide" refers to titanium dioxide (TiO2), titanium (III) oxide (Ti2O3) or titanium (II) oxide (TiO), preferably titanium dioxide (TiO2). "Viscosity" means a measure of a substance's resistance to velocity under an applied force per unit surface, expressed in centipoise (cP). In one embodiment, viscosity is measured at a temperature of 20°C or 25°C.

[0028] method The present invention relates to a method for producing a pigment for cosmetics. In one embodiment, the present invention relates to a method for producing a hydrophobic and / or oleophobic pigment. In one embodiment, the present invention relates to a method for producing a pigment with both hydrophobic and oleophobic properties (i.e., an omniphobic pigment).

[0029] In one embodiment, the method of the invention comprises the step of preparing an acidic aqueous solution comprising or consisting of metal oxide particles and poly(β-(1→4)-D-glucosamine), optionally partially or fully N-deacetylated (step (i)).

[0030] In one embodiment, the poly(β-(1→4)-D-glucosamine) is partially or fully deacetylated from poly(β-(1→4)-N-acetylglucosamine).

[0031] In one embodiment, the method of the present invention further comprises a step (step (ii)) of increasing the pH of the solution obtained in step (i) to about 12. In one embodiment, the method of the present invention further comprises a step (step (ii)) of increasing the pH of the solution obtained in step (i) to a range of 11 to 13, preferably to a range of 11.5 to 12.5, more preferably to 12.

[0032] In one embodiment, step (ii) results in the adsorption of said poly(β-(1→4)-D-glucosamine) onto metal oxide particles. In one embodiment, step (ii) results in the precipitation of metal oxide particles coated, preferably by adsorption, with said poly(β-(1→4)-D-glucosamine).

[0033] Step (i) In one embodiment, the solution in step (i) comprises pure water.In one embodiment, the solution in step (i) comprises deionized water.

[0034] In one embodiment, the solution in step (i) comprises an acid. In one embodiment, the solution in step (i) comprises a Lewis acid. In one embodiment, the solution in step (i) comprises a Bronsted acid. In one embodiment, the solution in step (i) comprises an organic acid, preferably a carboxylic acid, such as, but not limited to, methanoic acid, ethanoic acid (or acetic acid), propanoic acid, butanoic acid, pentanoic acid, hexanoic acid or heptanoic acid.

[0035] In one embodiment, the solution in step (i) has a pH of less than 7, preferably in the range of 0-6.

[0036] In one embodiment, the metal oxide particles are selected from titanium oxide, iron oxide, zinc oxide, zirconium oxide, yellow iron oxide, black iron oxide, red iron oxide, chromium oxide, and chromium hydroxide; preferably titanium oxide particles.

[0037] In one embodiment, the metal oxide particles have a diameter in the range of 10 nm to 100 μm, preferably 20 nm to 100 μm, 30 nm to 100 μm, 40 nm to 100 μm, 50 nm to 100 μm, 60 nm to 100 μm, 70 nm to 100 μm, 80 nm to 100 μm, 90 nm to 100 μm, 100 nm to 100 μm, 110 nm to 100 μm, 120 nm to 100 μm, 130 nm to 100 μm, 140 nm to 100 μm, 150 nm to 100 μm, 160 nm to 100 μm, 170 nm to 100 μm, 180 nm to 100 μm , 190nm to 100μm, 200nm to 100μm, 250nm to 100μm; 300nm to 100μm, 350nm to 100μm, 400nm to 100μm, 450nm to 100μm, 500nm to 100μm, 550nm to 100μm, 600nm to 100μm, 650nm to 100μm, 700nm to 100μm, 750nm to 100μm, 800nm ​​to 100μm, 850nm to 100μm, 900nm to 100μm, 950nm to 100μm, or 1000nm to 100μm.

[0038] In one embodiment, the metal oxide particles have a size in the range of 1 μm to 100 μm; preferably in the range of 20 μm to 60 μm; and more preferably have a size of about 40 μm.

[0039] In one embodiment, the metal oxide particles have a size in the range of 1 μm to 100 μm; preferably, 1 μm to 90 μm, 1 μm to 80 μm, 1 μm to 70 μm, 1 μm to 60 μm, 1 μm to 50 μm, 1 μm to 40 μm, 1 μm to 30 μm, 1 μm to 20 μm, or 1 μm to 10 μm. In one embodiment, the metal oxide particles have a size in the range of 1 μm to 100 μm; preferably, 20 μm to 100 μm, 30 μm to 100 μm, 40 μm to 100 μm, 50 μm to 100 μm, 60 μm to 100 μm, 70 μm to 100 μm, 80 μm to 100 μm, or 90 μm to 100 μm. In one embodiment, the metal oxide particles have a size of about 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100 μm.

[0040] In one embodiment, the poly(β-(1→4)-D-glucosamine) is N-acetylated, poly(β-(1→4)-N-acetyl-D-glucosamine).

[0041] In one embodiment, the partially N-deacetylated poly(β-(1→4)-ND-glucosamine) is a random copolymer of β-(1→4)-N-acetyl-D-glucosamine and β-(1→4)-D-glucosamine (i.e., poly[(β-(1→4)-N-acetyl-D-glucosamine)-co-(β-(1→4)-D-glucosamine)]).

[0042] In one embodiment, the partially N-deacetylated poly(β-(1→4)-D-glucosamine) has a degree of deacetylation in the range of more than 50% to 99%; preferably in the range of 75% to 95%; more preferably in the range of 75% to 85%. In one embodiment, the degree of deacetylation is in the range of more than 50% to 90%; preferably in the range of more than 50% to 80%; more than 50% to 70%; or more than 50% to 60%. In one embodiment, the degree of deacetylation is in the range of 60% to 100%; preferably in the range of 70% to 100%; more preferably in the range of 80% to 100%; or in the range of 90% to 100%. In one embodiment, the degree of deacetylation is about 55, 60, 65, 70, 75, 80, 85, 90, 95 or 100%.

[0043] In one embodiment, the poly(β-(1→4)-D-glucosamine) has a mass average molar mass (Mw) in the range of 10,000 Da to 500,000 Da; preferably 30,000 Da to 300,000 Da; more preferably 40,000 Da to 200,000 Da. In one embodiment, the poly(β-(1→4)-D-glucosamine) has a mass average molar mass (Mw) in the range of 40,000 Da to 500,000 Da; preferably 50,000 Da to 400,000 Da. In one embodiment, the poly(β-(1→4)-D-glucosamine) has a weight average molar mass (Mw) in the range of 40,000 Da to 400,000 Da; preferably 40,000 Da to 350,000 Da, 40,000 Da to 300,000 Da, 40,000 Da to 250,000 Da, 40,000 Da to 200,000 Da, 40,000 Da to 150,000 Da, 40,000 Da to 100,000 Da, or 40,000 Da to 50,000 Da.In one embodiment, the poly(β-(1→4)-D-glucosamine) has a molecular weight of 50,000 Da to 400,000 Da; preferably 60,000 Da to 400,000 Da, 70,000 Da to 400,000 Da, 80,000 Da to 400,000 Da, 90,000 Da to 400,000 Da, 100,000 Da to 400,000 Da, 110,000 Da to 400,000 Da, 120,000 Da to 400,000 Da. a, 130,000Da~400,000Da, 140,000Da~400,000Da, 150,000Da~400,000Da, 160,000Da~400,000Da, 170,000Da~40 0,000Da, 180,000Da~400,000Da, 190,000Da~400,000Da, 200,000Da~400,000Da, 210,000Da~400,000Da, 220,00 0Da~400,000Da, 230,000Da~400,000Da, 240,000Da~400,000Da, 250,000Da~400,000Da, 260,000Da~400,000Da, 270,000Da~400,000Da, 280,000Da~400,000Da, 290,000Da~400,000Da, 300,000Da~400,000Da, 310,000Da~400, In one embodiment, the poly(β-(1→4)-D-glucosamine) has a weight average molar mass (Mw) in the range of 50,000 Da to 190,000 Da. In one embodiment, the chitosan has a mass average molar mass (Mw) in the range of 50,000 Da to 190,000 Da (chitosan A). In one embodiment, the poly(β-(1→4)-D-glucosamine) has a mass average molar mass (Mw) in the range of 310,000 Da to 380,000 Da.

[0044] In one embodiment, the poly(β-(1→4)-D-glucosamine) has a viscosity in the range of 10 cP to 2000 cP; preferably 40 cP to 800 cP; more preferably 50 cP to 350 cP, measured at about 25° C. In one embodiment, the poly(β-(1→4)-D-glucosamine) has a viscosity in the range of 20 cP to 300 cP, 200 cP to 800 cP, or 800 cP to 2000 cP, measured at about 25° C.In one embodiment, the poly(β-(1→4)-D-glucosamine) has a molecular weight of about 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 310, 320, 330, 340, 350, 360, 370, 380, 390, 400, 410, 420, 430, 440, 450, 460, 470, 480, 490, 500, 510, 520, 530, 540, 550, 560, 570, 580, 590, 600, 610, 620, 630, 640, 650, 660, 670, 680, 690, 700, 710, 720, 730, 740, 750, 760, 770, 780, 790, 800, 810, 820, 830, 840, 850, 860, 870, 880, 890, 900, 910, 920, 930, 940, 950, 960, 970, 980, 990, 1000, 1010, 1020, 1030, 1040, 1050, 1060, 1070, 1080 , 1090, 1100, 1110, 1120, 1130, 1140, 1150, 1160, 1170, 1180, 1190, 1200, 1210, 1220, 1230, 1240, 1250, 1260, 1270, 1280, 1290, 1300, 1310, 1320, 1330, 1340, 1350, 1360, 1370, 1380, 1390, 1400, 1410, 1420, 1430, 1440, 1450, 1460, 1470, 1480, 1490, 1500, 1510, 1520, 1530, 1540, 1550, having a viscosity of 1560, 1570, 1580, 1590, 1600, 1610, 1620, 1630, 1640, 1650, 1660, 1670, 1680, 1690, 1700, 1710, 1720, 1730, 1740, 1750, 1760, 1770, 1780, 1790, 1800, 1810, 1820, 1830, 1840, 1850, 1860, 1870, 1880, 1890, 1900, 1910, 1920, 1930, 1940, 1950, 1960, 1970, 1980, 1990 or 2000 cP.

[0045] In one embodiment, the weight ratio of metal oxide particles to poly(β-(1→4)-D-glucosamine), optionally partially or fully deacetylated, is in the range of greater than 0 to 20; preferably in the range of 1 to 15; and more preferably about 10. In one embodiment, the weight ratio of metal oxide particles to poly(β-(1→4)-D-glucosamine), optionally partially or fully deacetylated, is about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20.

[0046] In one embodiment, the amount of poly(β-(1→4)-D-glucosamine), optionally partially or fully deacetylated, is in the range of greater than 0% to 20% by weight; preferably in the range of 1% to 15% by weight; more preferably about 3% or 10% by weight, based on the total weight of the poly(β-(1→4)-D-glucosamine) and metal oxide particles. In one embodiment, the amount of poly(β-(1→4)-D-glucosamine), optionally partially or fully deacetylated, is about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, or 20% by weight, based on the total weight of the poly(β-(1→4)-D-glucosamine) and metal oxide particles.

[0047] In one embodiment, the chitosan in the solution ranges from 1% to 10% by weight, preferably 3% or 10% by weight, based on the total weight of the chitosan and TiO2 particles. In one embodiment, the chitosan in the solution is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10% by weight, based on the total weight of the chitosan and TiO2 particles.

[0048] In one embodiment, step (i) is carried out at a temperature in the range of 1° C. to 40° C., preferably at a temperature in the range of 10° C. to 30° C.; more preferably at a temperature of about 20° C. In one embodiment, step (i) is carried out at a temperature of about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39 or 40° C.

[0049] Step (ii) In one embodiment, step (ii) comprises or consists of increasing the pH of the solution obtained in step (i) above.

[0050] In one embodiment, the step of increasing the pH of the solution is carried out with a hydroxide, preferably potassium hydroxide, more preferably with a solution of potassium hydroxide at a concentration of about 1 mol / L.

[0051] In one embodiment, the step of increasing the pH of the solution obtained in step (i) above increases the pH to about 12, 13 or 14.

[0052] In one embodiment, step (ii) does not comprise or consist of increasing the pH of the solution obtained in step (i) with the aim of obtaining a pH below 12.

[0053] In one embodiment, step (ii) is carried out at a temperature in the range of 1° C. to 40° C., preferably at a temperature in the range of 10° C. to 30° C.; more preferably at a temperature of about 20° C. In one embodiment, step (ii) is carried out at a temperature of about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39 or 40° C.

[0054] In one embodiment, step (ii) does not include heating. In one embodiment, step (ii) does not include heating at a temperature greater than 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C.

[0055] Other steps In one embodiment, the method of the present invention further comprises a washing step, hi one embodiment, the washing step is carried out with water.

[0056] In one embodiment, the method of the present invention further comprises a drying step, hi one embodiment, the drying step is carried out at a temperature in the range of 20°C to 70°C; preferably in the range of 30°C to 60°C; more preferably in the range of about 40°C to 55°C.

[0057] In one embodiment, the method of the present invention provides metal oxide particles having adsorbed poly(β-(1→4)-D-glucosamine) chains, optionally partially or fully deacetylated. In one embodiment, the method of the present invention provides pigment particles in powder form. In one embodiment, the method of the present invention provides individualized pigment particles.

[0058] Pigments The present invention also relates to cosmetic pigments. In one embodiment, the cosmetic pigments are hydrophobic and / or oleophobic. In one embodiment, the cosmetic pigments have both hydrophobic and oleophobic properties (i.e., the pigments are omniphobic).

[0059] In one embodiment, the cosmetic pigment comprises or consists of metal oxide particles, optionally with partially or fully deacetylated poly(β-(1→4)-D-glucosamine) adsorbed thereto. In one embodiment, the cosmetic pigment comprises or consists of metal oxide particles, optionally with partially or fully deacetylated poly(β-(1→4)-N-acetyl-D-glucosamine) adsorbed thereto. In one embodiment, the cosmetic pigment comprises or consists of metal oxide particles, optionally with partially or fully deacetylated poly(β-(1→4)-D-glucosamine) chains adsorbed thereto.

[0060] In one embodiment, a cosmetic pigment, preferably omniphobic, is obtainable by the process of the present invention as defined above.

[0061] Cosmetic Composition The present invention also relates to a composition comprising a cosmetic pigment as defined above. In particular, the present invention relates to a composition comprising a cosmetic pigment, preferably omniphobic, obtainable by the inventive process as defined above.

[0062] In one embodiment, the composition is a cosmetic composition. In one embodiment, the composition comprises a cosmetically acceptable base. In one embodiment, the cosmetically acceptable base is in the form of a gel, paste, cream, lotion, emulsion, stick, shampoo, powder, aerosol, film, or patch.

[0063] In one embodiment, the amount of cosmetic pigment in the composition ranges from greater than 0% to 90% by weight, based on the total weight of the composition.

[0064] In the present invention, the composition of the present invention may be used in combination with at least one cosmetic agent selected from fatty acids, organic solvents, gelling agents, softening agents, surfactants, synthetic detergents, gelling agents, fragrances, emulsifiers, opacifiers, stabilizers, foaming agents, chelating agents, preservatives, sunscreens, essential oils, pigments, mineral fillers, or any compound used in cosmetics.

[0065] In the present invention, the compositions of the present invention may be used in combination with at least one active ingredient.

[0066] Skin improvement method The present invention also relates to a method for improving the skin comprising using the cosmetic composition defined above.

[0067] In one embodiment, the skin improvement method comprises applying the cosmetic composition defined above to the skin of a subject in need of improvement as a single application.In one embodiment, the cosmetic composition of the present invention is applied to the skin of a subject in need of improvement at least once a month, preferably twice a month, more preferably once a week; more preferably, the composition of the present invention is applied only once a week.In one embodiment, the cosmetic composition of the present invention is applied to the skin of a subject in need of improvement at least once a day.

[0068] In one embodiment, the skin improvement method is for improving the skin tone of a subject.In one embodiment, the skin improvement method is for reducing the shine of the skin of a subject.

[0069] use The present invention also relates to the use of a cosmetic pigment as defined above, which is preferably omniphobic.

[0070] In one embodiment, the omniphobicity of the cosmetic composition of the present invention maintains the retention of said pigment on the skin of a subject for an extended period of time.

[0071] In one embodiment, the cosmetic pigment of the present invention is resistant to sebum and / or sweat secreted by the skin of a subject.

[0072] In one embodiment, the cosmetic pigment of the present invention is incompatible with water and / or oil, hi one embodiment, the cosmetic pigment of the present invention is incompatible with oil, such as cyclopentasiloxane (known as D5) or the ester isononyl isononanoate.

[0073] In one embodiment, the omniphobicity of the cosmetic composition of the present invention facilitates deposition of the cosmetic pigment onto the skin.

[0074] In one embodiment, the cosmetic pigments of the present invention are non-toxic to humans and / or the environment.

[0075] Working Example The present invention is further illustrated by the following examples. Abbreviation ℃: Celsius temperature cP: Centipoise Da: Dalton D5: Decamethylcyclopentasiloxane h: time Hg: mercury KOH: Potassium hydroxide M: moles per liter (mol / L) mL: milliliter TiO2: Titanium dioxide μm: micrometer

[0076] material and method All solvents and chitosan were purchased from the chemical company Sigma Aldrich. TiO2 pigments with an average diameter of 40 μm were purchased from the companies Miyoshi France or Sigma Aldrich. Three chitosans with the following characteristics were investigated: [Table 1]

[0077] Part 1 - Chemical Synthesis Example 1: Method for producing the omniphobic pigment of the present invention As the first step (step 1), prepare 100 mL of an acidic aqueous solution containing acetic acid, chitosan, and dispersed TiO2 particles. The chitosan in the solution ranges from 1 wt% to 10 wt%, preferably 3 wt% or 10 wt%, relative to the total weight of chitosan and TiO2 particles. Magnetically stir the solution until complete dissolution of chitosan A, B, or C.

[0078] Then, under pH measurement control, an aqueous solution of potassium hydroxide (1 M) is added to the solution previously prepared in step 1. When the reaction medium has a pH of approximately 12, the addition of KOH is stopped and the reaction medium is left stirring for 72 hours.

[0079] Finally, the reaction medium is centrifuged and washed by centrifugation cycles with water. The powdered pigment particles are removed and dried at a temperature between 45°C and 55°C under a reduced pressure of less than 50 mmHg.

[0080] Tests are then carried out by thermogravimetric analysis (ATG) and infrared spectroscopy (ATR) to characterize the chitosan adsorbed on the TiO2 surface. The ATG results compared to TiO2 particles without chitosan demonstrate that the method of the present invention gives a layer of chitosan adsorbed on the surface of the TiO2 particles. The infrared region of the powder obtained by the method defined above is 1100 cm -1 and 3000 cm -1 The characteristic peaks of chitosan are clearly shown.

[0081] Part 2 - Physicochemical tests Example 2: Hydrophobicity of the pigments obtained from the method of the present invention The objective is to demonstrate that the pigment particles obtained by the method defined in Example 1 (i.e. the method comprising an alkalization step at pH=12) are hydrophobic compared to TiO2 particles without any treatment and compared to methods in which the alkalization step is carried out at pH=6, 7 or 10.

[0082] 2.1. Use of the pigment particles obtained by the method of the present invention (pH=12) For this purpose, several types of powders were dispersed in vials containing pure water: Sample 1: Powder of TiO2 particles without any treatment ["TiO2"]; Sample 2: powder of TiO2 particles adsorbed with chitosan A and washed once ["TiO2+LV"]; Sample 3: powder of TiO2 particles adsorbed with chitosan A and washed four times ["TiO2+LV x4"]; Sample 4: powder of TiO2 particles adsorbed with chitosan B, washed once ["TiO2+MV"]; Sample 5: Powder of TiO2 particles adsorbed with chitosan B, washed four times ["TiO2+MV x4"].

[0083] The results in Figure 1 show that: When the TiO2 particles are not coated with chitosan, the particles disperse uniformly in water and exhibit hydrophilic properties; and When the -TiO2 particles are coated with chitosan, whether it is chitosan A, B or C, because they are hydrophobic, the particles aggregate and settle to the bottom of the vial in the form of a white powder.

[0084] Thus, this experiment demonstrates that the method of the present invention results in hydrophobic pigment particles as opposed to uncoated TiO2 particles.

[0085] 2.2. Comparison with particles obtained at pH = 6 or 7 The same experiments as in paragraph 2.1. were carried out with particles obtained from a process having an alkalinization step at pH 6 or 7 and compared with particles obtained from the process of the invention (alkalinization step at pH 12).

[0086] The results in FIG. 2 show that the particles of the present invention are hydrophobic, contrary to the particles obtained by the method in which the alkalinization step is carried out at pH=6 or 7, which are hydrophilic and therefore evident in FIG. 2 as the particles are still dispersed in the solution.

[0087] 2.3.Comparison with particles obtained at pH = 10 A comparison in water between particles obtained from a process with an alkalinization step at pH 10 and an equimolar ratio of TiO2 and chitosan, and particles obtained from the process of the present invention (alkalinization step at pH 12) was also performed.

[0088] Firstly, it was observed that the final products between the two methods were different: the method with the step at pH 10 produced a dense, hard-to-grind solid pink material, whereas the product obtained by the method of the present invention produced a particulate material in the form of a white powder.

[0089] The behavior of these products in water is similarly different: - the product of the process having an alkalinization step at pH 10 retains the morphology of a solid block, The product of the process of the invention is in the form of hydrophobic, individualized white particles (powder).

[0090] Thus, this experiment demonstrates that the method of the present invention results in hydrophobic pigment particles as opposed to the method with an equimolar pH 10 step. Indeed, the product obtained from the method with the pH 10 step is not compatible with cosmetic applications as a pigment requiring a powder form such as the present invention.

[0091] Example 3: Oleophobic properties of the pigments obtained from the method of the present invention The objective is to demonstrate that the pigment particles obtained by the method defined in Example 1 (i.e. the method comprising an alkalization step at pH=12) are oleophobic compared to TiO2 particles without any treatment and compared to methods in which the alkalization step is carried out at pH=6, 7 or 10.

[0092] 3.1. Use of the pigment particles obtained by the method of the present invention (pH=12) For this purpose, several types of powders were dispersed in vials containing a mixture of pure water and the ester isononyl isononanoate: Sample 1: Powder of TiO2 particles without any treatment ["TiO2"]; Sample 2: powder of TiO2 particles adsorbed with chitosan A and washed once ["TiO2+LV"]; Sample 3: powder of TiO2 particles adsorbed with chitosan A and washed four times ["TiO2+LV x4"]; Sample 4: powder of TiO2 particles adsorbed with chitosan B, washed once ["TiO2+MV"]; Sample 5: Powder of TiO2 particles adsorbed with chitosan B, washed four times ["TiO2+MV x4"].

[0093] The results in Figure 3 show that: - When the TiO2 particles are not coated with chitosan, the particles are uniformly dispersed only in water, and only a part of them coats the walls of the upper oil phase (the ester isononyl isononanoate); and When the -TiO2 particles are coated with chitosan, whether it is chitosan A, B or C, the particles are excluded from both the water and ester isononyl isononanoate phases and settle to the bottom of the vial in the form of a white powder.

[0094] Thus, this experiment demonstrates that the method of the present invention results in hydrophobic and oleophobic pigment particles as opposed to uncoated TiO2 particles.

[0095] 3.2. Comparison with particles obtained at pH = 6 or 7 The same experiments as in paragraph 3.1. were carried out with particles obtained from a process having an alkalinization step at pH 6 or 7 and compared with particles obtained from the process of the invention (alkalinization step at pH 12).

[0096] In the case of water, contrary to the particles obtained by methods in which the alkalinization step is carried out at pH=6 or 7, the particles are not hydrophobic (they are in the aqueous phase), which is contrary to the results of the present invention, which show that the particles have both hydrophobic and oleophobic properties.

[0097] 3.3. Comparison with particles obtained at pH = 10 The same experiment as in paragraph 3.1. was carried out using particles obtained from a process with an alkalinization step at pH 10 using equal mass concentrations of chitosan and TiO2 and compared with particles obtained from the process of the present invention (alkalinization step at pH 12).

[0098] In the case of water, the results show that the particles of the present invention remain in powder form and exhibit both hydrophobic and oleophobic properties, contrary to the particles obtained by a process in which the alkalinization step is carried out at pH=10 and the product appears in a blocky or flocculent form and cannot be converted into a pigment useful for cosmetic applications.

Claims

1. 1. A method for producing an omniphobic cosmetic pigment, comprising: (i) preparing an acidic aqueous solution containing metal oxide particles selected from titanium oxide, iron oxide, zinc oxide, zirconium oxide, yellow iron oxide, black iron oxide, red iron oxide, and chromium oxide and poly(β-(1→4)-D-glucosamine), wherein the poly(β-(1→4)-D-glucosamine) is acetylated or partially or completely deacetylated; and (ii) increasing the pH of the solution obtained in step (i) to 12 in order to adsorb the poly(β-(1→4)-D-glucosamine) onto metal oxide particles and to precipitate the resulting poly(β-(1→4)-D-glucosamine)-coated metal oxide particles.

2. The method of claim 1 , wherein the metal oxide particles are titanium oxide particles.

3. The method of claim 1 or claim 2, wherein the metal oxide particles have a size in the range of 100 nm to 100 μm.

4. The method according to any one of claims 1 to 3, wherein the poly(β-(1→4)-D-glucosamine) is fully deacetylated or partially N-deacetylated.

5. 5. The method of claim 4, wherein the poly(β-(1→4)-D-glucosamine) is partially deacetylated and has a degree of deacetylation ranging from 70% to 99%.

6. 6. The method according to any one of claims 1 to 5, wherein the poly(β-(1→4)-D-glucosamine) has a mass-average molar mass (Mw) in the range of 40,000 Da to 500,000 Da.

7. 7. The method of any one of claims 1 to 6, wherein the amount of poly(β-(1→4)-D-glucosamine) ranges from greater than 0% to 20%.

8. The method of any one of claims 1 to 7, wherein the acidic aqueous solution comprises an acid.

9. An omniphobic cosmetic pigment obtained by the method according to any one of claims 1 to 8, said omniphobic cosmetic pigment being in the form of a hydrophobic and oleophobic powder and comprising or consisting of titanium oxide particles to which chitosan chains are adsorbed.

10. A cosmetic composition comprising the omniphobic cosmetic pigment of claim 9 and a cosmetically acceptable base.

11. The composition of claim 10, wherein the cosmetically acceptable base is anhydrous.

12. 12. The composition according to claim 10 or 11, in the form of an aqueous gel, an oily gel, a paste, a cream, a lotion, an emulsion, a stick, a soap, a foam, a shampoo, a compact powder, a loose powder, a nail polish, a cosmetic mask, an aerosol, a film, a serum, an emulsion, or a patch.

13. A cosmetic skin improvement method comprising the use of the omniphobic cosmetic pigment according to claim 9 or the cosmetic composition according to any one of claims 10 to 12 in a subject in need thereof.

14. The method for improving skin according to claim 13, wherein the composition is administered to the skin of a subject in need thereof once a day.

15. Use of the cosmetic composition according to any one of claims 10 to 12 in make-up, skin care, sun care, hair care, manicure, toiletries, baby care or pet care.

Citation Information

Patent Citations

  • Cosmetic pigment coated with chitosan and production thereof

    JP1987223108A

  • Solid cosmetic

    JP1991099006A

  • Novel inorgano-bioorganic nanocomposite materials, their preparation and use

    WO2010128204A1